PENGARUH KONSELING TERHADAP HARGA DIRI KLIEN HIV/AIDS DI KLINIK VOLUNTARY COUNSELING AND TESTING (VCT) DI RSUD. ABDUL MOELOEK PROVINSI LAMPUNG TAHUN 2018 - Triyoso Triyoso; Yusuf Yusuf; Muahammad Arief Budiman (Holistik Jurnal Kesehatan, 2019)
ABSRACT : SELF ESTEEM OF PATIENT WITH HIV / AIDS: IMPLICATION OF COUNSELING AT CLINIC VOLUNTARY COUNSELING AND TESTING (VCT) ABDUL MOELOEK HOSPITAL - PROVINCE OF LAMPUNG 2018 Background: HIV prevalence in Indonesia is commonly still low, but in Indonesia it has been classified as a country with concentrated epidemic level that is the prevalence of more than 5% in certain sub-populations. Cases of HIV / AIDS in Indonesia from year to year tend to increase. The number of new cases of HIV in Indonesia has increased over the last three years, in 2011 cases of 21,031 HIV cases, in 2012 as many as 21,511 cases and in 2013 as many as 29,037 cases. Purpose: Knowing that of self esteem of HIV / AIDS client: implication of counseling at clinic voluntary counseling and testing (vct) abdul moeloek hospital - province lampung 2018. Methods: Quantitative research type with experimental analytic design with Pre Experiment approach and experimental design will use with one group pretest - posttest design. Population were all patient with HIV / AIDS at clinic Voluntary Counseling and Testing (vct) Abdul Moeloek hospital - Province of Lampung with sample of 18 respondents and purposive sampling technique. The statistical analysis used dependent T test. Results: Knowning that differences in self-esteem among patient with HIV / AIDS before and after counseling were 13,433, and standard deviation of 5,270. The test results obtained p-value = 0,000. Conclusion: There is influence of counseling on self esteem among patient with HIV / AIDS at Clinic Coluntary Counseling and Testing (VCT) Abdul Moeloek Hospital Province Lampung 2018. Suggestions in this study to management of clinic Voluntary Counseling and Testing (VCT) especially in counseling department to help patient to improving their self-esteem and giving motivation to their life.Pendahuluan: Prevalensi HIV di Indonesia secara umum memang masih rendah, tetapi di Indonesia telah digolongkan sebagai negara dengan tingkat epidemik yang terkonsentrasi yaitu adanya prevalansi lebih dari 5% pada sub populasi tertentu. Kasus HIV/AIDS di Indonesia dari tahun ke tahun cenderung meningkat. Jumlah kasus baru HIV di Indonesia mengalami peningkatan selama tiga tahun terakhir, pada tahun 2011 kasus HIV  sebanyak 21.031 kasus, pada Tahun 2012 sebanyak 21.511 kasus dan Tahun 2013 sebanyak 29.037 kasus.Tujuan: Untuk mengetahui pengaruh konseling terhadap harga diri klien HIV/AIDS di klinik Voluntary Counseling and Testing (VCT)  di RSUD. Abdul Moeloek Provinsi Lampung Tahun 2018.Metode: Jenis penelitian kuantitatif dan rancangan analitik eksperimental dengan pendekatan Pra Experiment dan rancangan eksperimen yang digunakan adalah one group pre test - post test desaign. Populasi dalam penelitian ini adalah seluruh penderita HIV/AIDS Lampung periode Juli s/d November Tahun 2017 sebanyak 96 orang, dan sampel sebanyak 18 responden dengan teknik purposive Sampling. Uji statistik yang digunakan adalah uji t dependent.Hasil : Diketahui perbedaan rata-rata harga diri klien HIV/AIDS sebelum dan sesudah diberikan konseling sebesar 13,433 , dan standar deviasi sebesar 5,270. Hasil uji diperoleh nilai p= (0,000 < 0,05).Kesimpulan : Ada pengaruh konseling terhadap harga diri klien HIV/AIDS di klinik Voluntary Counseling and Testing (VCT) RSUD Abdul Moeloek Provinsi Lampung Tahun 2018. Saran dalam penelitian ini  memberikan masukan pada manajemen klinik VCT terutama pada bagian bimbingan dan konseling untuk meningkatkan harga diri dan memotivasi kehidupan pasien.